Agricultural extension: Global status and performance in selected countries - Davis, Kristin E.; Babu, Suresh Chandra; Ragasa, Catherine (International Food Policy Research Institute, 2020)
Agricultural transformation and development are critical to the livelihoods of more than a billion small-scale farmers and other rural people in developing countries. Extension and advisory services play an important role in such transformation and can assist farmers with advice and information, brokering and facilitating innovations and relationships, and dealing with risks and disasters. Agricultural Extension: Global Status and Performance in Selected Countries provides a global overview of agricultural extension and advisory services, assesses and compares extension systems at the national and regional levels, examines the performance of extension approaches in a selected set of country cases, and shares lessons and policy insights. Drawing on both primary and secondary data, the book contributes to the literature on extension by applying a common and comprehensive framework — the “best-fit” approach — to assessments of extension systems, which allows for comparison across cases and geographies. Insights from the research support reforms — in governance, capacity, management, and advisory methods — to improve outcomes, enhance financial sustainability, and achieve greater scale. Agricultural Extension should be a valuable resource for policymakers, extension practitioners, and others concerned with agricultural development.